Exploring the influence of regional economic pillars on library service equity in Indonesia - Andjar Prasetyo,; Mohamad Miftah,; Irwantoro,; Muhammad Hanif Abdillah,; Wahyudiyono,; Wahab,; Mulyani Mudis Taruna,; A.M. Wibowo,; Ndoheba Kenda,; Siswanto,; Basori, (Malaysian Journal of Library and Information Science, 2024)
This study investigates how various factors - innovation capabilities, labour market conditions, health, business dynamics, ICT adoption, and market size - affect the distribution of library services across 34 provinces in Indonesia. Using multiple linear regression analysis, the study found that overall, these factors significantly influence library service distribution (F = 10.558, p < 0.001, R² = 0.701). Specifically, higher innovation capabilities, better health conditions, and greater ICT adoption positively impact the availability of library services. Conversely, challenges in the labour market, fluctuating business dynamics, and larger market size are associated with reduced library service distribution. The findings highlight the critical role of health and technology policies in promoting fair access to library services throughout the country.